Remembering K. J. Ratnam: indigenising political solutions and structural challenges in postcolonial Southeast Asia - Chong, Alan (2024)
Professor K. J. Ratnam was an iconic scholar who left behind an indelible mark on his staff and students during his tenure as Head of the Department of Political Science at the University of Singapore. Critical in this regard were his thoughts on managing plural, multiracial entities such as Malaysia and Singapore.